Altered fractionation diminishes importance of tumor volume in oropharyngeal cancer: Subgroup analysis of ARTSCAN‐trial. Issue 8 (20th March 2020) - Adrian, Gabriel; Gebre‐Medhin, Maria; Kjellén, Elisabeth; Wieslander, Elinore; Zackrisson, Björn; Nilsson, Per
Abstract: Background: A large tumor volume negatively impacts the outcome of radiation therapy (RT). Altered fractionation (AF) can improve local control (LC) compared with conventional fractionation (CF). The aim of the present study was to investigate if response to AF differs with tumor volume in oropharyngeal cancer. Methods: Three hundred and twenty four patients with oropharyngeal cancer treated in a randomized, phase III trial comparing CF (2 Gy/d, 5 d/wk, 7 weeks, total dose 68 Gy) to AF (1.1 Gy + 2 Gy/d, 5 d/wk, 4.5 weeks, total dose 68 Gy) were analyzed. Results: Tumor volume had less impact on LC for patients treated with AF. There was an interaction between tumor volume and fractionation schedule ( P = .039). This differential response was in favor of CF for small tumors and of AF for large tumors. Conclusion: AF diminishes the importance of tumor volume for local tumor control in oropharyngeal cancer.